2019
DOI: 10.1155/2019/5960563
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren, Fosinopril, and Their Outcome on Renin-Angiotensin-Aldosterone System (RAAS) in Rats with Thyroid Dysfunction

Abstract: Background and Objectives. Thyroid hormones have an important role in the growth and development of various tissues including the kidney, which is the major site of renin release and the consequent angiotensin and aldosterone formation. Therefore any derangement in thyroid function can result in abnormal functioning in the renin-angiotensin-aldosterone system. The current study was undertaken to find the impact of using a direct renin inhibitor (Aliskiren) and an angiotensin-converting enzyme inhibitor (Fosino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Aldosterone, a mineralocorticoid synthesized by aldosterone synthase from cholesterol, regulates the balance of electrolytes and water and is an important part of the renin-angiotensin-aldosterone system (RAAS) (Chandra et al, 2015). Thyroid dysfunction also affects the RAAS system and cortisol levels (Dizaye and Mustafa, 2019;Farhadi and Dizaye, 2019;Li et al, 2021). The thyroid and adrenal glands are regulated by the hypothalamic-pituitary axis to maintain normal metabolism, and any damage to the adrenal cortex can aggravate thyroid disease.…”
Section: Frontiers In Pharmacologymentioning
confidence: 99%
“…Aldosterone, a mineralocorticoid synthesized by aldosterone synthase from cholesterol, regulates the balance of electrolytes and water and is an important part of the renin-angiotensin-aldosterone system (RAAS) (Chandra et al, 2015). Thyroid dysfunction also affects the RAAS system and cortisol levels (Dizaye and Mustafa, 2019;Farhadi and Dizaye, 2019;Li et al, 2021). The thyroid and adrenal glands are regulated by the hypothalamic-pituitary axis to maintain normal metabolism, and any damage to the adrenal cortex can aggravate thyroid disease.…”
Section: Frontiers In Pharmacologymentioning
confidence: 99%
“…Clinical trials have demonstrated a strong antihypertensive and organoprotective (cardioprotective, renoprotective) role for the renin inhibitor [104,105]. It has been shown to be very good at regulating blood pressure in hyperthyroid rats [106]. The use of aliskiren showed a decrease in the antidiuretic effect of renin [107].…”
Section: Direct Renin Inhibitorsmentioning
confidence: 99%
“…Like captopril, fosinopril competitively inhibits ACE thereby it decreases the formation of the potent vasoconstrictor, angiotensin 2. The latter is one of the main factors in in hypertension induced tissue damage (pubchem/compound 172198) and [S. A. S. Farhadi and K. F. Dizaye (2019)]. Diminishing the angiotensin 2 production with suppresing its production implicitly also lowers the cytokine production and the synthesis of new ACE2 receptors [S. Wassmann and G. Nickenig (2006)].…”
Section: H4rmentioning
confidence: 99%